Conversation Analysis of Video-Mediated Communication: Interactional Repair of Distortion in Long-Distance Couples' Video Calls - Rintel, Sean (2015)
Ethnomethodology and the related fields of Conversation Analysis and Membership Categorisation Analysis investigate how the local production of practical, social understandings is a situated achievement. This is typically undertaken through a close analysis of video or audio of naturally-occurring activities, with the aid of transcripts to pin down precise sequences of actions. This exemplar illustrates how this approach can be used to explore interaction via technology, in this case video-mediated communication. The data is provided by Dr Sean Rintel, collected while undertaking his dissertation at the University at Albany, State University of New York and subsequently re-analysed for later publication. He recruited couples in existing long-distance relationships to try video calling, and created an automated remote recording system to capture all their video calls with their consent. As was the case then, and is still common now, domestic video calls often involve moments where the audio or video are distorted. Audio may be delayed, garbled, or missing. Video may be pixelated, frames dropped, frozen, or missing. Sometimes the audio and video are desynchronised. Collectively these issues are termed audio/video distortions. Audio/video distortions arose as an endogenous issue for all couples – that is, they were not introduced by the researcher, rather they were an internally-generated part of the medium. His research thus developed around how the couples repaired these distortions as a material issue in their conversations and the conduct of their relationships. In this exemplar, Sean explains gathering, transcribing, and analysing naturally-occurring video calling data. This exemplar will be useful for those who want to understand the ramifications of methodological choices when building a case for a particular argument about interactional practices in a technological context.
Rintel, S. (2015). Conversation Analysis of Video-Mediated Communication: Interactional Repair of Distortion in Long-Distance Couples’ Video Calls. Sage Research Methods. DOI: http://dx.doi.org/10.4135/9781473947481